The Mechanisms of Instrumental Music Playing in Preserving Cognitive Function in Adulthood - Almuthiiah, Khadijah; Bayanaka, Aldhiya Azmy; Dewi, Artu Alycia Laksmi; Andiyani, Dinda Zahra Putri; Alkautsar, Mohammad Saddam; Harahap, Herpan Syafii; Briliansy, Briliansy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Adulthood is divided into three stages: young adulthood, middle adulthood, and older adulthood. Middle adulthood (40-65 years) is the phase where the balance between growth and neurocognitive development begins. In this phase, prevention of cognitive decline is necessary by strengthening cognitive reserves through brain stimulation through musical activities. This study used a literature review method. In this article, we conducted a search using electronic databases such as PubMed, Google Scholar, ScienceDirect, ResearchGate, and the National Institute of Health (NIH). The review found that playing music can increase dopamine in the reward system and inhibit the hypothalamic-pituitary-adrenal (HPA) axis, which can improve motivation, attention, memory, and learning processes, thus strengthening cognitive function. Findings from Balinese gamelan and flute players indicate increased alpha and beta brainwave activity, which stimulate executive function, memory, and motivation. Therefore, playing traditional Indonesian music has the potential to improve cognitive abilities as a form of prevention of neurodegenerative disorders in adulthood. It was recommended that playing music in middle adulthood will improve cognitive function by playing traditional music.